2009
DOI: 10.1021/jf802226n
|View full text |Cite
|
Sign up to set email alerts
|

Nutriomic Analysis of Fresh and Processed Fruit Products. 2. During in Vitro Simultaneous Molecular Passages Using Caco-2 Cell Monolayers

Abstract: Many studies have used Caco-2 cell monolayers as human intestinal absorption models. However, only a few studied digested foods, instead of pure standard compounds. Moreover, beneficial and nutritional molecules (nutriome) have not been investigated simultaneously. The present study explored nutriome passages from digest solution of fresh, dried, and juiced tomato, mango, and papaya using Caco-2 cell monolayers in apical-->basolateral directions. A validation method using complementary TEER and P(app) values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…Transport study of organic acids by Caco-2 cells It is established from the literature that an acceptable TEER value for Caco-2 cell monolayers should be from 200 to 1,000 ohm/cm 2 [34]. Others studies have considered that acceptable TEER values for bioassays were[400 ohm/cm 2 [25,35]. Lower values indicate that tight junctions between cells are not developed enough or are damaged such that some small molecules could pass via a paracellular route to the basolateral chamber.…”
Section: In Vitro Digestion and Release Of Organic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transport study of organic acids by Caco-2 cells It is established from the literature that an acceptable TEER value for Caco-2 cell monolayers should be from 200 to 1,000 ohm/cm 2 [34]. Others studies have considered that acceptable TEER values for bioassays were[400 ohm/cm 2 [25,35]. Lower values indicate that tight junctions between cells are not developed enough or are damaged such that some small molecules could pass via a paracellular route to the basolateral chamber.…”
Section: In Vitro Digestion and Release Of Organic Acidsmentioning
confidence: 99%
“…The authors found some citric and malic acids in the basolateral chamber, which is not the case in the present study. This could be explained by the fact that the cells may metabolically consume different organic acids depending on other components released from the relevant fruit or vegetable [35].…”
Section: In Vitro Digestion and Release Of Organic Acidsmentioning
confidence: 99%
“…Many food preparation methods act as a source of contamination. For example, chopping of food can result in contamination of food if the equipment and surfaces are not sufficiently clean between meal preparations [44][45][46]. Chopping breaks down cell walls, releasing cell proteins for use by microbes [40].…”
Section: Microbiological Effectsmentioning
confidence: 99%
“…Some food presentation methods may also increase the chances of food contamination. For example, providing food in a scattered or buried format, particularly when food particles are chopped, will increase the likelihood that dirt and bacteria are consumed by the animal [45]. Similarly, impaling food items onto exhibit furnishings is likely to drive microbes into the food item and could increase chances of contamination.…”
Section: Microbiological Effectsmentioning
confidence: 99%
“…Increased paracellular permeability, via the modulation of tight junctions, has been reported after consumption of a meal especially in the presence of glucose[ 47 ] and alanine[ 48 ]. Using Caco 2 models, food components such as plant extracts[ 49 - 51 ] and isolated food components[ 52 - 54 ] have been shown to increase paracellular permeability with a the resultant flux in macromolecules, such as mannitol[ 51 , 55 , 56 ]. These authors, including Kosińska et al [ 57 ], postulated that food components could be safe alternatives to reversibly ‘open’ tight junctions in order to enhance the absorption of molecules of interest.…”
Section: Introductionmentioning
confidence: 99%